2007
DOI: 10.1016/j.jpainsymman.2006.11.008
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label, Multi-Dose Efficacy and Safety Study of Intramuscular Tetrodotoxin in Patients with Severe Cancer-Related Pain

Abstract: Cancer pain is a prevalent and serious public health issue, and more effective treatments are needed. This study evaluates the analgesic activity of tetrodotoxin, a highly selective sodium channel blocker, in cancer pain. A Phase IIa, open-label, multicenter, dose-escalation study of intramuscular tetrodotoxin was conducted in patients with severe, unrelieved cancer pain. The study design called for six ascending dose levels of intramuscular tetrodotoxin, administered over a four-day treatment period in hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 30 publications
2
64
0
1
Order By: Relevance
“…A range of other symptoms, including irritation at the administration site, were also reported. The adverse events presented during successive cycles were similar to those described during the first cycle, and the range and prevalence of events reported in the present study were similar in nature to those reported in previous trials 14,15 .…”
Section: Adverse Eventssupporting
confidence: 88%
See 2 more Smart Citations
“…A range of other symptoms, including irritation at the administration site, were also reported. The adverse events presented during successive cycles were similar to those described during the first cycle, and the range and prevalence of events reported in the present study were similar in nature to those reported in previous trials 14,15 .…”
Section: Adverse Eventssupporting
confidence: 88%
“…Second, in patients who describe an analgesic effect, relief of chronic cancer pain is persistent within successive treatment cycles up to and beyond 1 year, without evidence of tolerance: the anti-nociceptive effect of ttx is maintained for an average of 3 weeks, and this pain relief does not diminish with repeated cycles of the drug. Previous studies have reported the range of acute toxicity with administration of ttx at the dose used in the present work 14,15 . Typically, toxicity has been mild and primarily sensory, with transient peri-oral numbness or tingling as the predominant experience.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is, therefore, perhaps surprising that tetrodotoxin, which blocks most subtypes of sodium ion channels, is also in clinical trials. Most of the clinical work has been in Canada with patients suffering from severe cancer-related pain (Hagen et al, 2007(Hagen et al, , 2008(Hagen et al, , 2011. Results show some promise, with some patients noting improvements in symptoms, but more extensive testing may prove to be more demanding.…”
Section: Trials and Tribulationsmentioning
confidence: 99%
“…Therefore, higher forms of animals and humans are more sensitive to TTX, which can be toxic at extremely low concentrations (70) . The minimum lethal dose for humans is 2 mg (71,72,73,26,74) .…”
Section: Downloaded By [António Raposo] At 05:58 25 July 2015mentioning
confidence: 99%